L’appropriation des TIC par les diasporas : analyse des répercussions potentielles dans les pays d’origine - Jonathan Stebig; Yveline Deverin (Netcom)
Information and communication technologies (ICT) seem to modify the organisation of the Diasporas. This re-organisation of the migrant’s networks transforms the contact with families living in the homeland. Thus, the telecentre becomes an information and communication crossroad, resulting in inter-connection between the homeland and the different location of the Diaspora. New generations, which have a better knowledge of these tools, are the first intermediary within their countries. Therefore, that “mediator” roll for new generations imply further responsibilities in terms of politic, economy, and information, responsible of potentials changes in homeland traditional organisation.